The Effect of Learning Model Cycle 5E Combined with Student Science Project Activities to the Skills of Science Process and Scientific Attitude of Grade XI Students of SMAN 14 Padang - Heffi Alberida; Lani Viora Cecilia; Fitri Arsih (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2018)
The aim of this research was to investigate effect of 5E learning cycle model combined with science project on science-process skills and scientific attitudes. This research was based on problem of SMAN 14 Padang students whose scieence-process skills and scientific attitudes wasn’t optimally developed as a result of teacher-centered learning activity. A quasi-experimental design which was randomized control group posttest only design implemented have participants were recruited from among 3rd grade students of SMAN 14 Padang. The sample of this research had choosen by purposive sampling technique. Results of study reveal that there is significant difference between experimental and control group students’ science-process skills and scientific attitudes scores.